Protectionist Threats and Foreign Direct Investment - Robert Feenstra; Harris Dellas; Bruce A. Blonigen (University of California, Department of Economics, 1996)
The recent literature on quid pro quo foreign direct investment (FDI) suggests that FDI may be induced by the threat of protection, and further, that FDI may be used as an instrument to defuse a protectionist threat. This paper uses a panel data set of 4-digit SIC level observations of Japanese manufacturing FDI into the United States in the 1980s to explore these hypotheses empirically. We find strong statistical support for the hypothesis that higher threats of protection lead to greater FDI flows, and post-regression simulations find that a rise in the expected probability of protection from five to ten percent means over a 30 percent rise in next-period FDI flows for an average industry. In addition, there is evidence that non-acquisition FDI by the Japanese had success in defusing the threat of an escape clause investigation in future periods.
Keywords: 330